2017
DOI: 10.4172/2155-9929.1000317
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors of Transient Tachypnea of Newborn

Abstract: Background: Early diagnosis of transient tachypnea of newborn (TTN) is important for early treatment and good prognosis, but it is misdiagnosed with some diseases t hat occur in neonates like neonatal sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Özkiraz et al, found lactate might be useful for clinicians at first-level hospitals for decision making to refer the TTN patient to the secondary or tertiary level neonatal intensive care unit before the clinical situation is worsened [21]. Similarly, Farragy and Soliman found lactate can be used for early diagnosis of TTN and early treatment with a better prognosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Özkiraz et al, found lactate might be useful for clinicians at first-level hospitals for decision making to refer the TTN patient to the secondary or tertiary level neonatal intensive care unit before the clinical situation is worsened [21]. Similarly, Farragy and Soliman found lactate can be used for early diagnosis of TTN and early treatment with a better prognosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is a parenchymal lung disorder created due to delayed absorption of fetal lung fluid. TTN occurs in 1% -3% of the all births; TTN presents in the early hours of life and usually improves within 24 to 72 hours, but some of the affected infants rarely develop sever respiratory distress, which indicate malignant TTN (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%